2015
DOI: 10.1128/aac.03629-14
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Penicillin Use in Mexico and Brazil: Analysis of the Impact of Over-the-Counter Restrictions

Abstract: c During 2010, Mexico and Brazil implemented policies to enforce existing laws of restricting over-the-counter sales of antibiotics. We determined if the enforcement led to more appropriate antibiotic use by measuring changes in seasonal variation of penicillin use. We used retail quarterly sales data in defined daily doses per 1,000 inhabitant-days (DDD/TID) from IMS Health from the private sector in Mexico and Brazil from the first quarter of 2007 to the first quarter of 2013. This database contains informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
3
18
0
2
Order By: Relevance
“…There was a reduction in penicillin use among private pharmacies in Mexico after this initiative, with a more limited reduction in Brazil 298,299 . Further details about the impact of these initiatives are contained in Table 4.…”
Section: Brazil and Mexicomentioning
confidence: 99%
“…There was a reduction in penicillin use among private pharmacies in Mexico after this initiative, with a more limited reduction in Brazil 298,299 . Further details about the impact of these initiatives are contained in Table 4.…”
Section: Brazil and Mexicomentioning
confidence: 99%
“…; Faculty of Health Sciences, University of Brasília, Brasília, DF, Brazil b W e read with great interest the recently published paper by Santa-Ana-Tellez et al (1). In that work, the authors measured the changes in the seasonal variation in penicillin use before and after the restrictions on over-the-counter (OTC) antibiotic sales went into effect in Mexico and Brazil in 2010.…”
mentioning
confidence: 99%
“…Santa-Ana-Tellez et al (1) found that following the implementation of policies to restrict OTC sales of antibiotics, the seasonal variation in antibiotic usage decreased in Mexico but not in Brazil. On the basis of these findings, the authors concluded that in Mexico, the inappropriate use of penicillin may have diminished after the restrictions were enforced.…”
mentioning
confidence: 99%
“…Among many Latin American countries, including Brazil and Mexico, restrictions on OTC sales of antibiotics were implemented in 2010 (Santa- Ana-Tellez et al 2015). This included the requirement for a prescription for antibiotics to be dispensed even in private pharmacies.…”
Section: Antibiotic Prescribing and Dispensing In Pharmaciesmentioning
confidence: 99%
“…Brazil (private sector), Mexico and Serbia, and this will grow (Godman et al 2014;Moura et al 2015;Santa-Ana-Tellez et al 2015). We are already seeing a number of countries tighten illegal self-purchasing of antibiotics, e.g.…”
Section: Ambulatory Care (Settings Regions and Countries)mentioning
confidence: 99%